A study on the influence of internet addiction and online interpersonal influences on health-related quality of life in young Vietnamese. (December 2017) - Tran, Bach; Huong, Le; Hinh, Nguyen; Nguyen, Long; Le, Bao; Nong, Vuong; Thuc, Vu; Tho, Tran; Latkin, Carl; Zhang, Melvyn; Ho, Roger
Abstract Background Internet addiction (IA) is a common problem found in young Asians. This study aimed to study the influence of IA and online activities on health-related quality of life (HRQOL) in young Vietnamese. This study also compared the frequencies of anxiety, depression and other addiction of young Vietnamese with and without IA. Methods This study recruited 566 young Vietnamese (56.7% female, 43.3% male) ranging from 15 to 25 years of age via the respondent-driven sampling technique. Chi-squared, t -test and analysis of variance were used to compare young Vietnamese with and without IA. Regression analyses were used to examine the association between internet usage characteristics and HRQOL. Results Results from this cross-sectional study showed that 21.2% of participants suffered from IA. Online relationship demonstrated significantly higher influences on behaviors and lifestyles in participants with IA than those without IA. Participants with IA were more likely to have problems with self-care, difficulty in performing daily routine, suffer from pain and discomfort, anxiety and depression. Contrary to previous studies, we found that there were no differences in gender, sociodemographic, the number of participants with cigarette smoking, water-pipe smoking and alcohol dependence between the IA and non-IA groups. IA was significantly associated with poor HRQOL in young Vietnamese. Conclusion IA is a common problem among young Vietnamese and the prevalence of IA is the highest as compared to other Asian countries. Our findings suggest that gender may not play a key role in IA. This can be an emerging trend when both genders have equal access to the internet. By studying the impact of IA on HRQOL, healthcare professionals can design effective intervention to alleviate the negative consequences of IA in Vietnam.